Critical Thinking According to Islam and the West: An Analytical Review: Pemikiran Kritis Menurut Islam dan Barat: Satu Sorotan Analisis - Rosdi, Nur Afiqah; Ahmad, Khadher; Waehama, Muhammad Roflee (Jurnal Usuluddin, 2025)
The topic of critical thinking is often perceived as a complex subject with little need for in-depth discussion. Therefore, this article aims to examine the aspects of debates frequently addressed by previous scholars within the framework of critical thinking, while also identifying gaps in past studies. The data for this study were collected using a qualitative research method. These data were analyzed through both inductive and deductive methods to organize them based on appropriate themes and characteristics. The findings reveal that critical thinking is a skill required across all fields of knowledge. However, this skill cannot be effectively practiced without understanding the key elements involved in ensuring that the thinking process being conducted is indeed a critical one. Among the main elements are setting clear objectives, broadening perspectives, obtaining accurate information from authoritative and trusted sources, respecting differences, and acknowledging the truth. Various research approaches exist within the topic of critical thinking, including studies focusing solely on critical thinking, research that combines critical thinking with the Qur’an, studies merging critical thinking with hadith, and research that integrates critical thinking with religious aspects. Each of these research approaches contains gaps that can be filled with recent conceptual studies, offering new insights and perspectives compared to past trends in writing. This literature review also demonstrates significant differences between the concept of critical thinking in the West and Islam, particularly in the aspect of setting a purpose for engaging in critical thinking activities.